Rwanda : Ninth Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Rwanda's Ninth Review Under the Policy Support Instrument (PSI). Growth in 2017 was better than expected, supported in all areas except construction. Particularly notable was export performance, with goods exports rising by 58 percent, based on strong performance of both traditional and nontraditional exports. Inflation has remained below the central bank's 5 percent medium term target. External balances and reserve buffers have continued to improve faster than expected. Program performance is on track, with all continuous and end-December 2017 quantitative targets met as were all structural benchmarks, except the indicative target on contracting of new external debt by public enterprises. The IMF staff supports the completion of the Ninth Review under the PSI-supported program.